9.2k views
4 votes
–0.4(3x – 2) + StartFraction 2 x plus 4 Over 3 EndFraction for x = 4

User Karavolt
by
6.4k points

2 Answers

3 votes
0 also thanks for putting the whole thing most people don’t so it hard to understand lol
User ReganPerkins
by
5.3k points
3 votes

Answer:

0

Explanation:

Given

- 0.4(3x - 2) +
(2x+4)/(3) ← substitute x = 4 into the expression

= - 0.4(3(4) - 2) +
(2(4)+4)/(3)

= - 0.4(12 - 2) +
(8+4)/(3)

= - 0.4(10) +
(12)/(3)

= - 4 + 4 = 0

User Roshan Wijesena
by
6.0k points